2000
DOI: 10.1053/jpdn.2000.0150054
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in pediatric nursing: An international perspective

Abstract: The goal of this survey was to compare similarities and differences between two groups of pediatric nurses, a group from developing countries and a group from Israel, in confronting ethical issues and in the use of resources for support. Findings indicate similarities between the two groups in a majority of ethical situations that concern them in their work despite differences in cultural backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…The most commonly reported ethical dilemma of this study in terms of frequency and intensity was inappropriate behaviour on the part of the patient or family member towards a member of the staff. This problem seems to be consistent as the two previous studies that used the EDN also found that this dilemma was either ranked highest (Wagner & Hendel 2000) or one among the top five dilemmas (Wagner & Ronen 1996). This problem has also increased around the world with increased reporting of patient and family verbal and physical abuse to healthcare staff (Crilly et al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most commonly reported ethical dilemma of this study in terms of frequency and intensity was inappropriate behaviour on the part of the patient or family member towards a member of the staff. This problem seems to be consistent as the two previous studies that used the EDN also found that this dilemma was either ranked highest (Wagner & Hendel 2000) or one among the top five dilemmas (Wagner & Ronen 1996). This problem has also increased around the world with increased reporting of patient and family verbal and physical abuse to healthcare staff (Crilly et al.…”
Section: Discussionsupporting
confidence: 90%
“…The final version was reviewed for content validity by nurse ethicists. The questionnaire was used in three Israeli studies (Wagner & Ronen 1996, Hendel & Wagner 1998, Wagner & Hendel 2000). A pilot test was conducted to determine the tool’s feasibility and ease of administration.…”
Section: The Studymentioning
confidence: 99%
“…Another item found relatively high in both frequency and intensity was inappropriate behavior by patients and families against nurses. This problem seems to be consistent over time as the three previous studies that used the EDN that were conducted in a span of over 15 years also found that this dilemma was either ranked highest 19,30 or one among the top five dilemmas. 25 This problem has also increased around the world with increased reporting of patient and family verbal and physical abuse to healthcare staff.…”
Section: Discussionsupporting
confidence: 78%
“…It has been used in four previous Israeli studies. 19,27,29,30 The revised EDN for middle managers (EDN-MM) includes the original items of the EDN with an additional 22 items related to areas of concern to middle managers, for a total of 61 items. Each item is scored using two different Likert scales: one scale measures frequency (on a scale from 1 (never) to 4 (frequently)) and the second scale measures intensity (on a scale from 0 (not relevant) to 6 (extremely intense)).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation